2004
DOI: 10.1093/beheco/ari002
|View full text |Cite
|
Sign up to set email alerts
|

Female collared flycatchers adjust yolk testosterone to male age, but not to attractiveness

Abstract: The differential allocation hypothesis predicts that females invest more resources into reproduction when mating with attractive males. In oviparous animals this can include prefertilization decisions such as the production of larger eggs and the deposition of hormones, such as the steroid testosterone, into yolks. On the other hand, a compensatory hypothesis posits that females allocate more resources into the eggs when mated with males of inferior quality. In the present study, we show that free-living femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 44 publications
(61 reference statements)
5
64
0
1
Order By: Relevance
“…In addition, it has been revealed that the attractiveness of mates affects the concentration of egg yolk components thought to contribute to the early physical development of offspring, such as testosterone (Gil et al, 1999;Gil et al, 2004; but see Mazuc et al, 2003;Michl et al, 2005) and immune factors (Saino et al, 2002b). These findings confirm that females invest more in reproduction when the prospective fitness return is high.…”
Section: Introductionmentioning
confidence: 78%
“…In addition, it has been revealed that the attractiveness of mates affects the concentration of egg yolk components thought to contribute to the early physical development of offspring, such as testosterone (Gil et al, 1999;Gil et al, 2004; but see Mazuc et al, 2003;Michl et al, 2005) and immune factors (Saino et al, 2002b). These findings confirm that females invest more in reproduction when the prospective fitness return is high.…”
Section: Introductionmentioning
confidence: 78%
“…data). No within-clutch pattern of yolk androgens was found in a Hungarian population of the collared flycatchers (Michl et al, 2005), thus yolk androgen concentration in the middle egg should be a good proxy for the mean hormone level of a clutch. Even if within-clutch variation in hormone deposition would have occurred in some individuals of our study population, the third egg would still represent the medium concentration of the whole clutch, as long as the pattern of within-clutch variation is linear (as found in many studied species with significant within-clutch variation, e.g.…”
Section: The Cross-fostering Experimentsmentioning
confidence: 86%
“…In most species studied so far, including the collared flycatcher and its sister species the pied flycatcher (Ficedula hypoleuca), the between-clutch variation in yolk androgen levels is higher than the within-clutch variation (e.g. Reed and Vleck, 2001;Groothuis and Schwabl, 2002;Pilz et al, 2003;Tschirren et al, 2004;Michl et al, 2005;Müller et al, 2007b, Tobler et al, 2007T. Laaksonen, unpubl.…”
Section: The Cross-fostering Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, female effort has also been found to increase when females mate with a male that offers fewer benefits to offspring fitness. This phenomenon has been termed 'reproductive compensation' [2,[17][18][19][20][21][22][23] and has recently been suggested to be a special case of differential allocation, as female allocation is likely to fall on a continuum between positive and negative responses to male phenotype (e.g. attractiveness) [2,10,20].…”
Section: Introductionmentioning
confidence: 99%